Job satisfaction among selected academic librarians in North Sumatra - Ali, Muhammad; Santos, Herminia H. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1996)
This study aimed to conduct a survey of job satisfaction among selected academic librarians in North Sumatra, Indonesia.
Questionnaires were used as an instrument and distributed to 106 librarians. Of the number distributed, only seventy (66.04) librarians participated in the study. They covered the librarians from ten top public and private academic institutions, consisting of, forty one were from private and twenty nine were from public academic institutions.
Two type of tests were used in analyzing data, namely: Spearman Correlation Coefficients for testing the significant of overall satisfaction with age, status of employment, experience in library work, educational attainments and salaries (ordinal-ordinal). While Sex (gender) and civil status with overall satisfaction used Mann Whitney U-Test (nominal-ordinal). The final findings of the study are : age influenced environment, location of residence, promotion, and work related factors; sex (gender) influenced promotion, working relationship with institutions; civil status influenced environment and promotion; experience influenced work related factors, supervisors, environment, and colleagues; educational attainment influenced promotion, working relationship with institutions, and benefits; salaries influenced work-related factors, location of residence and promotion. Those are all the factors that influenced job satisfaction of academic librarians in North Sumatra. While other factors such as civil status does not influence colleagues, location of residence, supervisors, work related factors, working relationships with institutions and benefits; Sex does not influence location of residence, supervisors, work-related factors, benefits, colleagues, and environment; age does not influence colleagues, supervisors, benefits, working relationships with institutions; educational attainment does not influence environment, location of residence, supervisors, work related factors, and colleagues; status of employment does not influence environment, location of residence, promotions, supervisors, work related factors, working relationships with institutions, benefits, and colleagues; experience does not influence location of residence, promotions, working relationships with institutions, and benefits;, salary does not influence supervisors, working relationship with institutions, benefits, colleagues, and environment.
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Librarians--Job satisfaction--Indonesia--North Sumatra